Estetyczna przygoda sztuki - Wilkoszewska, Krystyna (Horyzonty Wychowania, 2017)
The notion of „art” and its understanding have undergonenumerous transformations over the centuries. New trends haveappeared. Simultaneously the functions assigned to art havebeen changing, beginning with those most practical and useful,through the reflection of reality, depicting the diversity of emotionsand experiences, the aesthetic function, to „presenting itself”.Nowadays art experiences another period of notional transformation.Therefore, a necessity arises to refrain from judgementin favour of formulating new adequate questions and depictingnew values carried by contemporary art